Alternatives for a research on the movement of Porto Alegre preschools - Verônica Regina Müller (Journal of Physical Education (Maringá), 2008)
The aim which stimulated and conducted this research was that of providing alternatives to pedagogy of movement within the public preschools in Porto Alegre. To foilow it\'s aim, this research examineci first, the most general context of the preschool. related to the movement, and secondly, the specific context of the public preschool in Porto Alegre. The data were obtained through observations within the classroom, a questionnaire with four open questions for thirty preschools teachers anci later, private interviews sith eight chosen teachers. The subject analysis was the method which founded and allowed to give meaning to the gathered data. Pedagogy of movement can be interpreted as a methodology which respects, values and explores the movement of the human being, and considers him a necessity, thus a natural means of the child\'s potentialities development. Results show that there are immediate alternatives shich define the objetives for this pedagogy and can since now be materialized through methods, activities, and some alike materiais bica, for instance, the participant group which chooses and plans it\'s activities; and makes profit form scraps as material. They also procalim the engagement of the Physical Education teacher for a permanent position, to develop specifically the psichomotor activities. There are general difficulties - common in many schools which impede the pedagogy of movement to be a reality in an ideal way within the public preschools. The alternatives for these dificulties are summed up in three words: modernization, valuation and organization of teachers within the intra, inter and extra school ambits. At last, it was concluded that the shown alternatives will be really considered of such a kind, if every teacher assumes them in form of real attitude day by day.